The impact of the SQ3R strategy (SURVEY - Question- Reading – Recite- Review) in the achievement of the students of the Faculty of Education in mathematics and the development of creative thinking skills. A semi-experimental study on the students of the (Journal of Hama University, 2020)
The objective of the research is to answer the following main question: What is the impact of the SQ3R learning strategy on the achievement of mathematics for the students of the basic education college at Mustansiriyah University and the development of their creative thinking skills. The researcher،s used the experimental method and applied the experimental study in the first semester of the academic year (2018-2019). On a sample of the students of the Faculty of Education at the University of Mustansiriyah, the sample were (44(students in two groups. experimental included 22 students and control group included 22. The research  tools were a test of the achievement of the tribal past and Torrance test of creative thinking Torrance verbal image (a) where the researcher studied their honesty and persistence and reached the final experience and experimentation within the Iraqi environment and reached the study of an important set of results summarized as follows:.1 There were no statistically significant differences in the scores of the students at the 0.05 level between the mean test scores in the experimental and control groups, which leads to the two groups being equal.• There are statistically significant differences in favor of the experimental group that used the SQ3R teaching strategy.3. There were statistically significant differences in the mean distance of the Torrance scale between the group of students of the experimental group and the group of students of the control group in the research sample and for the benefit of the experimental group. The study also issued a set of recommendations.